Can we predict which hospitalised patients are in their last year of life? A prospective cross-sectional study of the Gold Standards Framework Prognostic Indicator Guidance as a screening tool in the acute hospital setting. (September 2014) - O'Callaghan, Anne; Laking, George; Frey, Rosemary; Robinson, Jackie; Gott, Merryn
Background: Screening to identify hospital inpatients with a short life expectancy may be a way to improve care towards the end of life. The Gold Standards Framework Prognostic Indicator Guidance is a screening tool that has recently been advocated for use in the hospital setting. Aim: To assess the clinical utility of the Gold Standards Framework Prognostic Indicator Guidance as a screening tool in an acute hospital setting. Main outcome measures: Mortality at 6 and 12 months and sensitivity, specificity and predictive value of the Gold Standards Framework Prognostic Indicator Guidance at 1 year. Design, setting and participants: Prospective cross-sectional study of 501 adult inpatients in a tertiary New Zealand teaching hospital screened utilising the Gold Standards Framework Prognostic Indicator Guidance. Results: A total of 99 patients were identified as meeting at least one of the Gold Standards Framework Prognostic Indicator Guidance triggers. In this group, 6-month mortality was 56.6% and 12-month mortality was 67.7% compared with 5.2% and 10%, respectively, for those not identified as meeting the criteria. The sensitivity and specificity of the Gold Standards Framework Prognostic Indicator Guidance at 1 year were 62.6% and 91.9%, respectively, with a positive predictive value of 67.7% and a negative predictive value of 90.0%. Conclusion: The sensitivity, specificity and predictive values of the Gold Standards Framework Prognostic Indicator Guidance in this study are comparable to, or better than, results of studies identifying patients with a limited life expectancy in particular disease states (e.g. heart failure and renal failure). Screening utilising the Gold Standards Framework Prognostic Indicator Guidance in the acute setting could be the first step towards implementing a more systematic way of addressing patient need – both current unrecognised and future anticipated – thereby improving outcomes for this population.